FACTORS INFLUENCING CUSTOMERS’ LOYALTY TOWARDS GUESTS’ SATISFACTION IN INAYA PUTRI BALI HOTEL AND RESORT - Kadek Mega Amelia Nuka; Ni Nyoman Sri Astuti; Gede Ginaya; I Gusti Agung Mas Krisna Komala Sari; I Ketut Budarma (Politeknik Negeri Bali, 2018)
This study aims at determining factors and the dominant ones that affect customers’ loyalty in Inaya Putri Bali. The data was collected by applying purposive sampling method, with customer criteria which is long stay guests and guests’ repeaters as well as using questionnaires. Having been collected the questionnaires, it was obtained 100 respondents in Inaya Putri Bali. The data was analyzed using the method of factor analysis in SPSS 22 software with 20 items of questions. The result of factor analysis reveals that there are 5 factors influencing loyalty in Inaya Putri Bali, namely (a) guest satisfaction, (b) service quality, (c) product quality, (d) price and (e) brand. These five factors that are considered to be the service endeavor of every hotel employees involved which is affected significantly the customers’ loyalty due to an excellent performance of the employees. As a result, the customers are willing to return staying at Inaya Putri Bali for their next holiday in Bali.